PEMANFAATAN EDUGAME ISI PIRINGKU SEBAGAI MEDIA PENINGKATAN PENGETAHUAN IBU BALITA - Purwaningsih, Puji; Chairijah, Zumrotul; Sifai, Izzatul Alifah (PPM STIKES Adi Husada, 2023)
Introduction & Aim: Nutritional problems still need to be solved in various parts of Indonesia. Cases of nutrition can be excess nutrition or malnutrition. The phenomenon in Semarang Regency was the tendency for school-age children to be overweight. This overweight event indeed occurs several times. Child age is a vulnerable phase in nutritional problems because this causes the onset of a disease at the next age. This community service aims to increase understanding and skills in utilizing learning media through Edugame about my plate content. Method of Activity: This activity was carried out from the 3rd of June to the 3rd of July 2023 in Genuk district, Semarang Regency. The results of the questionnaire about the knowledge before and after the activity were analyzed using univariate analysis of frequency distribution. This community service activity was done in Posyandu (Integrated Services Post) for under-five children by involving village midwives, cadres, and 11 mothers having under-five children. Results: The results of this community service show that knowledge is increasing about my plate content after counseling or socialization. Discussion: This Edugame can be used as a media for health education to help the community increase understanding of a theme. This Edugame can be used to overcome the saturation of recipients of information, especially toddlers: it helps learn, motivates, fun educational media, and can increase creativity.